Is the link from working memory to analogy causal? No analogy improvements following working memory training gains. - J Elizabeth Richey (Public Library of Science (PLoS), 2014)
Analogical reasoning has been hypothesized to critically depend upon working memory through correlational data, but less work has tested this relationship through experimental manipulation. An opportunity for examining the connection between working memory and analogical reasoning has emerged from the growing, although somewhat controversial, body of literature suggests complex working memory training can sometimes lead to working memory improvements that transfer to novel working memory tasks. This study investigated whether working memory improvements, if replicated, would increase analogical reasoning ability. We assessed participants' performance on verbal and visual analogy tasks after a complex working memory training program incorporating verbal and spatial tasks. Participants' improvements on the working memory training tasks transferred to other short-term and working memory tasks, supporting the possibility of broad effects of working memory training. However, we found no effects on analogical reasoning. We propose several possible explanations for the lack of an impact of working memory improvements on analogical reasoning.